PENGARUH ADVERTISING ATTITUDE TERHADAP SHOPPING LOYALTY MELALUI IMPULSE BUYING PADA CARREFOUR GOLDEN CITY MALL MAYJEN SUNGKONO SURABAYA - WUNAS, RINI PRICILIA (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2012)
Modern retail industry in Indonesia now is starting to grow and this growth is expected to continue to experience significant growth. This study aims to examine the effect of Advertising Attitude through Impulse Buying toward Shopping Loyalty at Carrefour Golden City Mall Mayjen Sungkono Surabaya. The study design uses a causal study of 120 respondents with a take sample technique is non-probability sampling (non-probability sampling). Meanwhile, the analysis technique used is structural equation modeling (SEM) with LISREL program. Respondents were drawn from all customers who come and shopping at Carrefour Golden City Mall Mayjen Sungkono Surabaya. The results showed that: Advertising Attitude have effect to Impulse Buying and Shopping Loyalty, Impulse Buying have effect to Shopping Loyalty, and Advertising Attitude have effect to Shopping Loyalty through Impulse Buying